The knowledge of learning strategies as an alternative for the strengthening of heutagogical competences in university students in virtual mode - Aguilar-Gordón, Floralba del Rocío (2024)
The article analyses the importance of knowledge of learning strategies to develop heutagogical competences in virtual university students. The manuscript raises as a fundamental problem the lack of development of heutagogical competences or the necessary skills and abilities that allow university students to learn in an autonomous and self-directed way. In response to this problem, the author proposes a number of strategies such as problem-based learning, collaborative learning and the use of technology to foster autonomous and self-directed learning. She theorises some questions about the philosophical, sociological, psychological, and pedagogical foundations of learning strategies; she makes a conceptual approach to heutagogy, its characteristics, principles and history. It examines the pillars of education as the main reference for understanding the formulation of learning strategies with a view to achieving an integral education of the human being. It is research with a qualitative exploratory approach that is supported by theoretical level methods such as the analytical-synthetic method and the inductive-deductive method and empirical level methods such as the direct experience of the researcher, content analysis, documentary analysis and literature review. Relevant findings include the need to propose various intentional, autonomous, metacognitive, contextualised, active and duly evaluated learning strategies to support the development of heutagogical competences, contribute with mechanisms for the adaptation of students to social changes, promote self-learning, enhance the sense of commitment and internal motivation, and, ultimately, promote the development of critical-creative-propositive thinking.